Characteristics of wellness tourism users in “Merkur” Specialised Hospital - Đurađević, Marijana (Hotel and Tourism Management, 2017)
Wellness tourism is one of the selective forms of tourism with good prospects of development in our country, especially due to its wealth in spas and thermal mineral springs. Vrnja?ka Banja certainly is one of the spas that boasts the potential for the wellness tourism development. The synonym for Vrnja?ka Banja is the "Merkur" Specialised Hospital within which the first wellness center in Serbia opened. The aim of the paper is to look into the characteristics of tourists? demands in wellness tourism, primarily through the theoretical analysis of these characteristics as well as the characteristics of the users of the contemporary and wellness services offered by the "Merkur" Specialised Hospital. The detailed account of their characteristics will be provided through the analysis of the guest questionnaires on the services used at the wellness center in a certain period, as well as through the interviews with the users of the "Merkur" wellness center in a single day.